THE ROLE OF JOB BURN OUT, STRESS RESILIENCE ON CAREER DEVELOPMENT MEDIATED BY WORK-LIFE BALANCE AT PT. VIRQUARIA - Garavani Slamet, Angela; Purwani Setyaningrum, Retno (Jurnal Ilmu Manajemen (JIMMU), 2025)
This study aims to analyze the effect of job burnout and stress resilience on career development, with work-life balance as a mediating variable among employees of PT. VIRQUARIA in Bekasi Regency. This research uses a quantitative approach with an explanatory research type that seeks to test the relationships between variables in a structural model. The population in this study consists of all 200 employees of PT. VIRQUARIA, with a sampling technique using cluster sampling, resulting in a sample of 90 respondents. Data were collected through questionnaires and analyzed using SmartPLS 3.0. The results show that job burnout has no significant effect on career development, but it has a significant effect on work-life balance. Stress resilience does not have a direct effect on career development, but it significantly influences work-life balance. In addition, work-life balance has a positive and significant effect on career development. However, work-life balance does not mediate the relationship between job burnout or stress resilience and career development. These findings highlight the importance of maintaining a balance between work and personal life as a critical factor in supporting employees' career development.